KOMUNIKASI ANTAR BUDAYA DALAM BINGKAI TEORI-TEORI ADAPTASI - Edy Sumaryanto; Malik Ibrahim (Nusantara Hasana Journal, 2023)
Adaptation is a problem that needs to be solved from the study of intercultural communication because, when a person or group of people communicate with other parties who are culturally different, it can present problems between them. This research aims to describe the theories of intercultural communication adaptation. This research uses qualitative research methods with a library research approach. In this study, researchers used data analysis techniques in the form of analyzing the content of documentation. This analysis is a way to get the appropriate data, thus the strategy is to identify data from the bias of data characteristics, then the information is made systematically so that the object under study is able to provide perfect conclusions. The results of the research show that the theories of intercultural communication adaptation include: uncertainty reduction theory, anxiety theory or uncertainty management theory, acculturation and culture shock theory, and co-cultural theory.